(untitled) (Bangladesh Heart Journal, 2021)
Background: Obesity is now becoming a global epidemic. It is most of the times associated with hypertension, diabetes mellitus (DM), metabolic syndrome and dyslipidemia which are known risk factors for coronary artery disease (CAD). Coronary arteriosclerosis comprises a series of inflammatory responses at cellular and molecular level, whose reactions are stronger in obese patients. The objective of this study was to observe the association of obesity and raised inflammatory markers with CAD. Method: This cross-sectional study was carried out in the Department of Cardiology, Dhaka Medical College Hospital, Dhaka, Bangladesh, involving 668 patients of ischemic heart disease who underwent coronary angiography (CAG) from January 2017 to December 2017. Obesity was defined as body-mass index (BMI) ≥30.0 kg/m2. C-reactive protein (CRP) was measured as the inflammatory marker, and was considered as high if >10 mg/L. CAD was classified on the basis of CAG findings: insignificant if stenosis is <50% and significant if stenosis is ≥50%; and single-vessel, double-vessel, triple-vessel disease and normal coronaries according to number of vessels involved. Chi square test was used to analyze the categorical variables, and Pearson’s correlation coefficient was used to test the relationship between CRP and BMI in CAD patients. p values of <0.05 were considered as statistically significant. Results: Demographic characteristics like age, sex and educational status did not differ significantly between obese and non-obese patients. Risk factors for CAD were similar between obese and non-obese, as well as, between high-CRP (>10 mg/L) and non-high CRP (≤10 mg/L) groups, however, DM, hypertension and dyslipidaemia were significantly more common in obese and high-CRP groups than in non-obese and non-high CRP groups. Raised CRP was significantly more common in obese than in non-obese patients (56.9% vs. 47.9%, p=0.04). Significant positive correlation was found between CRP and BMI (r=0.228; p=0.001). Triple-vessel CAD was found significantly more commonly in obese group than in non-obese group (29.3% vs 24.4%, p=0.04), whereas normal coronaries were more common in nonobese than in obese counterpart. Obesity, high CRP (>10 mg/L), DM, and high HbA1c (≥6.5%) were found significant predictors of severe CAD (p <0.5) in multivariate logistic regression analysis. Conclusion: Obesity is associated with raised inflammatory marker in patients with CAD, and a significant positive association exists between obesity and inflammation and CAD. Future studies are needed to explore the impact of type of obesity and inflammation on CAD. Bangladesh Heart Journal 2021; 36(1): 9-16